L'expérience de l'infarctus du myocarde : tensions identitaires des malades et effets sur leur demande de soins - Marianne Lafitte (Nantes Université, 2019)
Many people who are victims of myocardial infarction do not call for help or differ the call, endangering themselves. These unadapted behaviors have been largely examinated, but the methods and results of the studies appear insufficient to understand what is being played intimately in patients who suffer a heart attack. We conducted a qualitative research in an epistemology of subjectivity and mobilizing the point of view in first person of patients, with the aim of exploring and understanding: (1) real-life experience of subjects during a heart attack, (2) the choices operated by victims of myocardial infarction during the crisis, (3) the mental phenomena that influence their decision to call for emergency services. We describe how identity tensions can influence patients' decision to call a health professional. Our re-search pursues an objective of improving patient education targeting subjective phenomena that determine choices of patients during a health crisis.